Determinants of Cash Holding in Consumer Non-Cyclicals Companies Listed on the Indonesia Stock Exchange - Osvaldo Xavier Veda; Ratieh Widhiastuti (Mandalika Journal of Business and Management Studies, 2026)
This study examines the effect of leverage, operating cash flow (OCF), and firm size on cash holding in Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The research was motivated by the importance of corporate liquidity management in maintaining operational stability amid post-pandemic economic uncertainty, inflationary pressures, and changes in monetary policy in Indonesia. This study employed a quantitative approach using secondary data obtained from audited annual financial statements. The sample consisted of 74 companies selected through purposive sampling, resulting in 296 balanced panel observations. Data analysis was conducted using panel data regression with the Random Effect Model (REM) as the selected estimation model based on the Lagrange Multiplier and Hausman tests. The results reveal that operating cash flow (OCF) has a positive and significant effect on cash holding, indicating that firms with stronger internally generated cash flows tend to maintain higher cash reserves. In contrast, leverage and firm size exhibit negative but insignificant effects on cash holding. Simultaneously, leverage, operating cash flow (OCF), and firm size significantly influence cash holding. However, the relatively low explanatory power of the model suggests that other financial and operational factors outside the model may also substantially influence corporate cash holding behavior. These findings suggest that operational cash generation plays a more important role in determining corporate cash reserves than debt structure or company scale. The study contributes to the corporate finance literature by providing empirical evidence on cash holding determinants in Indonesia’s Consumer Non-Cyclicals sector during the post-pandemic recovery period.